2001
DOI: 10.1046/j.0014-2956.2001.02543.x
|View full text |Cite
|
Sign up to set email alerts
|

A new siglec family member, siglec‐10, is expressed in cells of the immune system and has signaling properties similar to CD33

Abstract: The siglecs (sialic acid‐binding Ig‐like lectins) are a distinct subset of the Ig superfamily with adhesion‐molecule‐like structure. We describe here a novel member of the siglec protein family that shares a similar structure including five Ig‐like domains, a transmembrane domain, and a cytoplasmic tail containing two ITIM‐signaling motifs. Siglec‐10 was identified through database mining of an asthmatic eosinophil EST library. Using the Stanford G3 radiation hybrid panel we were able to localize the genomic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 39 publications
0
52
0
Order By: Relevance
“…*P Ͻ .0005; **P Յ .005; ***P Ͻ .05. member of the Siglec family expressed on eosinophils, albeit at much lower levels than on monocytes and natural killer (NK) cells. 9,23 Thus, it appears that Siglec-8 is most specific for eosinophils. Initial studies of Siglec-8 suggested that the molecule had an uncharacteristically short cytoplasmic tail with no known signaling motifs.…”
Section: Discussionmentioning
confidence: 99%
“…*P Ͻ .0005; **P Յ .005; ***P Ͻ .05. member of the Siglec family expressed on eosinophils, albeit at much lower levels than on monocytes and natural killer (NK) cells. 9,23 Thus, it appears that Siglec-8 is most specific for eosinophils. Initial studies of Siglec-8 suggested that the molecule had an uncharacteristically short cytoplasmic tail with no known signaling motifs.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Taking into account the expression pattern and binding properties of Siglec-10, it has the characteristics to be a ligand for endothelial VAP-1. Although the sequence match between the enriched peptide and Siglec-10 is not perfect, the sequence contained several amino acids with similar properties.…”
Section: Discussionmentioning
confidence: 99%
“…The cytosolic tails of most CD33-related Siglecs have two conserved tyrosine-based putative signaling motifs, one of which conforms to the immunoreceptor tyrosine-based inhibitory motif (ITIM), while the other is a putative motif of unknown function (1,9,10). It has been shown in some CD33-related Siglecs that the ITIM is the preferred docking site for the protein tyrosine phosphatase SHP-1 (27,32,36,41), and cross-linking of these Siglecs elicits negative signaling in the cells expressing these molecules (15,27,36,39,40). Although the expression pattern of CD33-related Siglecs and their function as signaling molecules suggest their involvement in the regulation of innate immunity, their in vivo function in a model organism has not been studied so far.…”
mentioning
confidence: 99%